Bandung City Communication and Information Service's Media Relations Strategy in Managing Publications in the Mass Media - Awal, Brilliant; Perbawasari, Susie; Lusiana, Elnovani (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2024)
The arrest of Bandung Mayor Yana Mulyana by the Corruption Eradication Commission (KPK) has sparked widespread media attention, which has been intensively reporting on the case. In response to this situation, the Bandung City Communication and Information Agency (Diskominfo) has strengthened its relationship with the mass media to maintain the image of the city government. This study analyzes the Diskominfo media relations strategy in managing publications amidst the crisis. A descriptive qualitative approach was used with data analysis techniques based on the Miles and Huberman model, including data reduction, data presentation, and conclusion. The findings show that Diskominfo utilizes various strategies to reduce negative images, such as press releases, press conferences, and cooperation with the media. The relationship between Diskominfo and the mass media is interpreted as mutually beneficial cooperation; the media obtains easier access to information, while Diskominfo can convey positive narratives to the public. However, this relationship raises concerns from the public regarding the potential for reducing media independence. In conclusion, Diskominfo's media relations strategy effectively manages the crisis, although a balance is needed to maintain transparency and independence of the news.